Evaluating the Use of Chemical Weapons for Capturing Prey by a Venomous Mammal, the Greater Slow Loris (Nycticebus coucang) - Grace Fuller; Wirdateti; K. A. I. Nekaris (Animals, 2024)
Few mammals are venomous, including one group of primates—slow (Nycticebus spp.) and pygmy (Xanthonycticebus spp.) lorises. Hypotheses for the evolutionary function of venom in these primates include defense from predators or ectoparasites, communication or competition with conspecifics, and the capture of prey. We tested the prey capture hypothesis in 75 trials with 22 wild-caught greater slow lorises (N. coucang) housed in a rescue center in Java, Indonesia. We experimentally offered the slow lorises arthropod prey items varying in size, escape potential, and toxicity and recorded venom-related and predatory behaviors using live and video observations. The slow lorises visually targeted arthropod prey, approached it quickly and efficiently, and captured it with a manual grasping motion. They rarely performed venom-related behaviors and seemed to do so in a defensive context. The slow lorises exhibited little variation in pre-capture behavior as a function of prey size or escape potential. In response to noxious prey, the slow lorises performed tongue-flicking and other investigative behaviors that indicate they are using chemosensory input to assess prey characteristics. These data suggest it is unlikely that slow lorises use chemical weapons to subdue arthropod prey and may support, instead, a defensive function for slow loris venom.